Performance characterization of an integrated cone‐beam CT system for dedicated gamma radiosurgery. Issue 9 (30th July 2018) - Sarfehnia, Arman; Ruschin, Mark; Chugh, Brige; Yeboah, Collins; Becker, Nathan; Cho, Young‐Bin; Lee, Young
Abstract : Purpose: This work describes the performance characterization of a cone‐beam CT‐guided radiosurgery device, the Gamma Knife ® Icon™. Methods: The performance tests have been categorized into: (a) image quality and mechanical integrity; (b) image coregistration fidelity; (c) adaptive treatment delivery quality; (d) high definition motion management performance characterization; (e) software communication performance testing of the integrated cone‐beam CT (CBCT) system. Results: All image quality performance characterization satisfied or exceeded manufacturer specifications. The image quality and mechanical stability of the CBCT system over a 3‐month period was within tolerance with negligible (<0.1°) detector tilt angle. The CBCT definition of the stereotactic space had a measured average discrepancy of 0.15–0.16 mm in x, y, and z directions. On average, the high definition motion management system performance was within 0.05 mm with a residual offset of 0.15 mm when large displacements in a given direction were taken. The adaptive treatment delivery component as measured with CBCT coregistration of daily setups against reference setup images was accurate to within 0.2°. Comprehensive end‐to‐end testing showed a total uncertainty of better than 0.2 mm in positioning and 0.4% in dosimetry for treatment of centrally located lesions. Conclusions: A set of system performance characterization tests spanning all aspects of the Gamma Knife Icon are presented. Overall, the system performance was in line with manufacturer specifications.